In a Manner of Speaking: How Reported Speech May Have Shaped Grammar - Spronck, Stef; Casartelli, Daniela (Frontiers in Communication, 2021)
We present a first, broad-scale typology of extended reported speech, viz. examples of lexicalised or grammaticalised reported speech constructions without a regular quotation meaning. These typically include meanings that are conceptually close to reported speech, such as THINK or WANT, but also interpretations that do not appear to have an obvious conceptual relation with talking, such as CAUSE or BEGIN TO. Reported speech may therefore reflect both concepts of communication and inner worlds, and meanings reminiscent of `core grammar', such as evidentiality, modality, aspect, (relational) tense and clause linking. We contextualise our findings in the literature on fictive interaction and perspective and suggest that extended reported speech may lend insight into a fundamental aspect of grammar: the evolution of verbal categories. Based on the striking similarity between the meanings of extended reported speech and grammatical categories, we hypothesise that the phenomenon represents a plausible linguistic context in which grammar evolved.